Enhancing Antioxidant Activity from Aquatic Plant Cymodocea nodosa for Cosmetic Formulation Through Optimized Ultrasound-Assisted Extraction Using Response Surface Methodology - Emna Chaabani; Sarra Mgaidi; Ameni Ben Abdennebi; Sarra Dakhlaoui; Majdi Hammami; Sawssen Selmi; Mohamed Zariat; Abdessalem Shili; Othmane Merah; Iness Bettaieb Rebey (Cosmetics)
This study aimed to enhance antioxidant extraction from the aquatic plant Cymodocea nodosa for cosmetic formulation through optimized ultrasound-assisted extraction using response surface methodology. The optimized conditions—30 min of extraction time, 30% ultrasonic power, and 25% hydro-ethanolic solvent—resulted in a high total phenolic content of 113.07 mg EAG/g DM and antioxidant activity of 67.02%. Chromatographic analysis revealed a rich profile of phenolic compounds, including sinapic acid (0.741 mg/g), myricetin (0.62 mg/g), and quercetin-3-O-rutinoside (0.3 mg/g), demonstrating the extract’s potent therapeutic properties. While the extract exhibited limited anti-inflammatory activity, it showed no cytotoxic effects on RAW 267.4 cells, ensuring its safety for cosmetic applications. The formulated cream maintained stable pH (6.58 to 6.6), consistent viscosity (5966.38 to 5980.6 cp), and minimal color changes over a 30-day period, indicating robust stability across various temperatures (4 °C, 25 °C, and 40 °C). These results confirm the potential of C. nodosa extracts to develop effective, stable, and eco-friendly cosmetic products, offering substantial benefits for skin health and emphasizing the importance of sustainable extraction processes in the cosmetics industry.